1994
DOI: 10.1128/mcb.14.10.6704
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel transcription factor that binds to and activates insulin control element-mediated expression.

Abstract: Pancreatic i-cell-type-specific transcription of the insulin gene is principally regulated by a single cis-acting DNA sequence element, termed the insulin control element (ICE), which is found within the 5'-flanking region of the gene. The ICE activator is a heteromeric complex composed of an islet at/-cell-specific factor associated with the ubiquitously distributed E2A-encoded proteins (E12, E47, and E2-5 showed that p-cell-specific transcription was regulated by 5'-flanking insulin DNA sequences (21). These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Furthermore, parallel increases were observed for a gene capable of inhibiting differentiation, ID-1, as well as other normally suppressed genes. In normal islets, ID-1 expression is low, but it is induced in isolated islets and ␤-cell lines cultured under high glucose conditions, with little effect in other cell types (11), and its forced expression can inhibit insulin promoter activity (36,37). These findings raise the possibility that increased ID-1 plays a role linking hyperglycemia to ␤-cell dedifferentiation in db/db mice.…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, parallel increases were observed for a gene capable of inhibiting differentiation, ID-1, as well as other normally suppressed genes. In normal islets, ID-1 expression is low, but it is induced in isolated islets and ␤-cell lines cultured under high glucose conditions, with little effect in other cell types (11), and its forced expression can inhibit insulin promoter activity (36,37). These findings raise the possibility that increased ID-1 plays a role linking hyperglycemia to ␤-cell dedifferentiation in db/db mice.…”
Section: Discussionmentioning
confidence: 64%
“…We first examined whether PDX-1 or XIHbox8 could synergize with E activator factors to stimulate transcription from an insulin gene reporter construct. These experiments were performed with HeLa cells, which lack endogenous PDX-1 (26, 32), ␤2 (33), and INSAF (47).…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to determine if the N-terminal conserved sequences of PDX-1 are important in functional interactions with the bHLH activators required in insulin E element-mediated transcription. The E element activator is a heteromeric complex composed of the generally distributed proteins (i.e., E2/5, E12, E47 [5,8,15,53], and HEB [42]) and distinct islet-enriched factors (␤2/NeuroD [25,33] and INSAF [47]). Previous studies have indicated that pancreatic ␤-cell-type-specific transcription of the insulin gene resulted from cooperative interactions between PDX-1 and the E activator proteins (16,38,50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICE activator is a heteromeric complex composed of the insulin activator factor (INSAF) proteins (34), which are uniquely distributed to ␣ and ␤ cells, and the generally expressed E2A-encoded basic helix-loop-helix (B-HLH) proteins, E12, E47, and/or E2-5 (9,16,32,35,38). The E2A proteins (E12, E47, and E2-5) are all very similar (21,22,42).…”
mentioning
confidence: 99%